Arthroscopic Curettage and Bone Grafting of Bone Cysts of the Talar Body - Tun Hing Lui, M.B.B.S.(HK), F.R.C.S.(Edin), F.H.K.A.M., F.H.K.C.O.S. (Arthroscopy Techniques, 2017)
Talar bone cysts can develop as a result of osteochondral lesions of the talus. This can be a source of deep ankle pain. Open debridement and bone grafting of the bone cysts requires extensive soft tissue dissection and malleolar osteotomy. Removal of normal cartilage of the talus is frequently required to approach the bone cysts. Alternatively, the cysts can be grafted arthroscopically with minimal disruption of the normal cartilage surface. The key to success is careful preoperative planning with a computed tomogram of the ankle. Bone cyst of the posterior half of the talar body can be grafted via posterior ankle endoscopy. Bone cyst of the anterior half of the talar body can be debrided and grafted via anterior talar osseous portals. The purpose of this technical note is to describe a minimally invasive approach of curettage and bone grafting of the talar bone cysts with preservation of the articular surfaces.